2016
DOI: 10.1590/s1806-37562016000000105
|View full text |Cite
|
Sign up to set email alerts
|

Alternative diagnoses based on CT angiography of the chest in patients with suspected pulmonary thromboembolism

Abstract: Objective: To determine the prevalence of alternative diagnoses based on chest CT angiography (CTA) in patients with suspected pulmonary thromboembolism (PTE) who tested negative for PTE, as well as whether those alternative diagnoses had been considered prior to the CTA. Methods: This was a cross-sectional, retrospective study involving 191 adult patients undergoing CTA for suspected PTE between September of 2009 and May of 2012. Chest X-rays and CTAs were reviewed to determine whether the findings suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
1
9
1
6
Order By: Relevance
“…This finding shows that PE is seen two decades earlier than in non-HIV patients where the mean age of presentation is 67-62 years. 5,6,7,9 This is in keeping with other literature on HIV-infected patients where the mean ages for PE were younger than the general population, ranging from 40 to 45 years. 2,3,10,11,12 Presenting symptoms in this study were typical of that described in the Prospective Investigation of Pulmonary Embolism Diagnosis (PIOPED II) trial, including shortness of breath, syncope, chest pain and haemoptysis -all of which are non-specific.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding shows that PE is seen two decades earlier than in non-HIV patients where the mean age of presentation is 67-62 years. 5,6,7,9 This is in keeping with other literature on HIV-infected patients where the mean ages for PE were younger than the general population, ranging from 40 to 45 years. 2,3,10,11,12 Presenting symptoms in this study were typical of that described in the Prospective Investigation of Pulmonary Embolism Diagnosis (PIOPED II) trial, including shortness of breath, syncope, chest pain and haemoptysis -all of which are non-specific.…”
Section: Discussionsupporting
confidence: 89%
“…A few previous studies on the HIV prevalence in PE-positive patients have reported much lower percentages in the general population of other countries, ranging from 9.5% to 24.6%. 5,6,7,9,14 This indicates that CTPAs are, indeed, a relevant investigation in the evaluation of respiratory distress in both HIV-infected and HIV-negative patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In Brazil, the estimated incidence is 0.6 cases per 1,000 inhabitants per year, while the worldwide incidence in 2003 was 0.5 cases per 1,000 inhabitants per year. 1,2 Cancer is a risk factor for both TEP and venous thromboembolism, and there is a four-times higher risk of developing TEP in cancer patients than in the general population. If the patient is undergoing chemotherapy, this risk increases up to six times.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2001 and 2009, the incidence of PTE increased from 29 to 78 cases per year; this increase is partly due to an increase in the number and quality of imaging tests, particularly chest CT angiography, as well as to incidental findings of pulmonary embolism on routine examinations for other diseases, such as cancer. 1 , 2 Despite technological advances, the diagnosis of PTE remains a challenge; autopsy studies have shown that the prevalence of PTE cases undiagnosed in life is 84.6%. 3…”
mentioning
confidence: 99%